Perbandingan Performa Reverse Proxy Caching Nginx dan Varnish Pada Web Server Apache - Muhammad Luthfi; Mahendra Data; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Web servers are now an essential part of both developing and newly started companies. Apache is the web application server with the most revenue in the world. Apache, however, has some drawbacks, one of which is that Apache is become slower when serving many requests continuously. One way to improve the performance of Apache web servers is by reverse proxy cahing. Of the many reverese proxy caching, Nginx and Varnish have the highest reputation. To find out the resource management and quality of service revese proxy caching Nginx and Varnish on the Apache web server will be tested by sending a number of requests to the web server. As a result, both servers with reverse proxy caching can outperform the Apache web server without reverse proxy caching on CPU usage and latency in the first 3 tests, whereas on Apache server load testing without reverse proxy caching it provides smaller latecy than Apache servers without revese Proxy cacahing. The comparison between Varnish reverse proxy caching and Nginx paired on the Apache web server, giving the Apache server results with reverse proxy caching Varnish performs better than the Apache server with Nginx reverse proxy caching.